Tinkers farm - Rabley, Stephen (Harlow, Essex, England : Addison Wesley Longman, 1998)
Jenny's friendship with a young Indian girl leads the Tinkers to a better life.
Cover title.
Adult.
Adult
Keywords: Farm life -- Fiction; Fathers and daughters -- Fiction; Friendship -- Fiction; Indians of North America -- Fiction; Readers for new literates; Farm life -- Fiction; Father-daughter relationship -- Fiction; Friendship -- Fiction; Historical fiction; Native Americans -- Fiction; Native Americans -- North America -- Fiction; Native Americans -- United States -- Fiction; Reading materials